SOLUTION TO PROMOTE THE IMPLEMENTATION OF SOCIAL SECURITY POLICY IN VIETNAM - Quy, Truong Thi Thanh (IJRDO - Journal of Social Science and Humanities Research, 2018)
During more than 30 years of renovation, Vietnam has realized the policy of socialist-oriented market economy development. Economic achievements have been made, such as rapid economic growth, rational economic structure transition, increasing per capita income, thus improving people's life. Besides, the Party and State have also promulgated social security policies for the benefit of the people. In all Congresses, the Communist Party of Vietnam has regularly emphasized the role of social security policy and the Party's determination to implement the policy.